Gambaran Mutu Jasa Pelayanan Kesehatan pada Pasien Rawat Jalan di Puskesmas Bintauna Kabupaten Bolaang Mongondow Utara - Iin Deliana Ishak; Adisti Aldegonda Rumayar; Ribka Elisabeth Wowor (Pusat Riset dan Inovasi Nasional, 2025)
Health centers as one of the health service facilities that are required to provide maximum service. Quality in the field of service is a measuring tool for consumer needs for the provision of services to determine how much profit will be obtained at an efficient cost so that consumer services can obtain health services. The quality of health services is a concept of quality measurement of service quality consisting of five dimensions, namely, reliability, assurance, tangibles, responsiveness and empathy. This study aims to determine the overview of the quality of health services based on five dimensions of health service quality for services to outpatients at the Bintauna Health Center, North Bolaang Mongondow Regency. This type of research is quantitative descriptive using a cross-sectional approach. The study was conducted for 12 days from March 4 to 19, 2025. The sample in this study was outpatients totaling 95 respondents with a sampling technique of accidental sampling. The results of this study indicate that the picture of the quality of health services that utilize outpatient services at the Bintauna Health Center, North Bolaang Mongondow Regency, is seen from 5 dimensions of the quality of health services that have been provided, namely the dimension of patient reliability which has a good assessment of 52 respondents (54.7%) and less good of 43 respondents (45%), the dimension of patient assurance which has a good assessment of 89 respondents (93.7%) and less good of 6 respondents (6.3%), the dimension of patient physical evidence which has a good assessment of 62 respondents (65.3%) and less good of 33 respondents (34.7%), the dimension of patient responsiveness which has a good assessment of 48 respondents (50.5%) and less good of 47 respondents (49.5%) and the dimension of patient empathy which has a good assessment of 51 respondents (53.7%) and less good of 44 respondents (46.3%). The conclusion of this study is that the quality of health services for outpatients at the Bintauna Health Center, seen as a whole from the 5 existing quality dimensions, can be categorized as good.